Endothelial plasticity governs the site-specific leukocyte recruitment in hepatocellular cancer - Salnikova, Olga; Breuhahn, Kai; Hartmann, Natalie; Schmidt, Jan; Ryschich, Eduard (International journal of cancer, 2013)
The correct programming of the endothelial cell phenotype is crucial for efficient leukocyte recruitment to tumor tissue. It has been previously described that T cells infiltrated hepatocellular cancer (HCC) tissue mainly in peritumoral, stromal and tumor border areas. In the current study, phenotype features of tumor endothelial cells and their potential impact on leukocyte recruitment were analyzed in murine tissue of HCC. In the murine model, proinflammatory stimulation with IL-1β induced leukocyte recruitment in the blood vessels of peripheral tumor areas and in nonmalignant liver tissue, but not in deeper tumor blood vessels. Furthermore, peripheral tumor endothelium, but not deeper tumor blood vessels exhibited a “normalized” hepatic sinusoidal endothelial cell (HSEC)-like phenotype with regard to the expression of adhesion molecules and liver sinusoidal endothelial markers. When tumor endothelial cells were isolated and incubated in vitro, their phenotype rapidly changed and became almost identical to normal hepatic endothelial cells. Interestingly, cytokine production in HCC was strongly dysregulated as compared to normal liver, with IL-1RN exhibiting the most prominent elevation. Experiments with isolated hepatic endothelial cells showed that IL-1RN effectively antagonized the activating action of IL-1β on the expression of adhesion molecules and T cell attachment. These novel insights indicate that tumor endothelium of HCC represents a plastic system that is susceptible to microenvironmental changes. The peritumoral and tumor border areas have distinct endothelial cell phenotype, which promotes leukocyte recruitment to HCC tissue.